Quadriceps Exercise Training in Unilateral Osteoarthrosis Knee: Isometric Versus Isotonic: Effectiveness of Isotonic Training for Improving Functional Mobility and Decreasing Pain in Unilateral Osteoarthritis Knee (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Objectives To investigate the efficacy of Isotonic training in decreasing pain, and increasing balance, walking speed functional mobility in Osteoarthritis Knee.Study design Comparative case control study.Methodology Two hundred (200) individuals with a diagnosis of OA Knee will be selected directly from Physiotherapy outpatient door CMJ University, Department of Physiotherapy, Shillong, Meghalaya. 50 will be qualified for study and are randomly assigned into two groups. Isotonic Exercise group (n = 25) and Isometric Exercise group (n = 25).Results Results indicate that both groups improved in all measures of pain, Balance, walking and functional outcomes. However, upon Intergroup analysis the mean changes in the score of BBS 20-meter walking time will highly significant across the two testing periods (at 6 week 12 week) for the Isotonic training group (FTT) with respect to Isometric training Group (TE).Conclusion Isotonic training on regular basis an effective rehabilitation program for improving functional mobility, balance, walking speed and decreasing pain in OA Knee.